Posttraumatic Cranial Cystic Fibrous Dysplasia. (25th August 2011) - Tomiyama, Arata; Aoki, Kazuya; Nakayama, Haruo; Izukura, Hideaki; Kimura, Hitoshi; Harashina, Jun-ichi; Ito, Keisuke; Hayashi, Morito; Saito, Norihiko; Sakurai, Takatoshi; Oharaseki, Toshiaki; Terada, Hitoshi; et al.
Abstract : A 14-year-old was girl admitted to our hospital with a subcutaneous mass of the occipital head. The mass had grown for 6 years, after she had sustained a head injury at the age of 6, and was located directly under a previous wound. Skull X-ray Photograph (xp), computed tomography (CT), and magnetic resonance imaging (MRI) showed a bony defect and cystic changes in the skull corresponding to a subcutaneous mass. Bone scintigraphy revealed partial accumulation. The patient underwent total removal of the skull mass, and the diagnosis from the pathological findings of the cyst wall was fibrous dysplasia (FD). The radiographic findings for cystic cranial FD can be various. Progressive skull disease has been reported to be associated with head trauma, but the relationship between cranial FD and head trauma has not been previously reported. Previous studies have suggested that c-fos gene expression is a key mechanism in injury-induced FD.